2014
DOI: 10.3892/ijo.2014.2516
|View full text |Cite
|
Sign up to set email alerts
|

miR-126 inhibits growth of SGC-7901 cells by synergistically targeting the oncogenes PI3KR2 and Crk, and the tumor suppressor PLK2

Abstract: Abstract. MicroRNA (miRNA)-126 (miR-126) was reported to be downregulated and to act as a tumor suppressor in cancers of the lung, cervix, bladder and prostate. However, the functions of miR-126 in gastric cancer appear to be diverse and are largely unknown. MiR-126 was reported to act as a tumor suppressor by targeting the Crk gene, or as an oncogene by targeting the SOX2 gene in gastric cancer. We identified that the expression of miR-126 was decreased in gastric cancer cell lines and tissues. PLK2, a tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 35 publications
2
39
0
Order By: Relevance
“…The potential role of miR-126 in targeting the PIK3R2 -mediated PI3K/Akt signaling pathway was further evaluated. The luciferase reporter assay showed that PIK3R2 was a direct target of miR-126 in bladder cancer, which is consistent with previous evidence suggesting that PI3KR 2 is a target of miR-126 19,24…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The potential role of miR-126 in targeting the PIK3R2 -mediated PI3K/Akt signaling pathway was further evaluated. The luciferase reporter assay showed that PIK3R2 was a direct target of miR-126 in bladder cancer, which is consistent with previous evidence suggesting that PI3KR 2 is a target of miR-126 19,24…”
Section: Discussionsupporting
confidence: 90%
“…The invasive potential of bladder cancer cells can be attenuated with increased miR-126 levels by mechanistically targeting disintegrin and metalloproteinase domain-containing protein 9 17,18. By synergistically targeting oncogenes ( PI3KR2 and adaptor protein Crk ) and tumor suppressors ( polo-like kinase 2 ), miR-126 was shown to have an inhibitory effect on the growth of gastric cancer cell lines 19. Mechanistically, silencing miR-126 may alter the activation of the PI3K/Akt pathway, suggesting an important regulatory role for miR-126 in PI3K/Akt pathway transduction, which is considered to play a major role in bladder carcinogenesis 20,21.…”
Section: Introductionmentioning
confidence: 99%
“…It has been noted that miR-126 inhibits the invasion of gastric cancer cells partially by targeting v-crk avian sarcoma virus CT10 oncogene homolog (Crk) (30). Liu et al reported that miR-126 inhibits the growth of gastric cancer cells by targeting phosphoinositide 3-kinase regulatory subunit 2, Crk and polo-like kinase 2 (31). Thus, the present study expands on the understanding of the miR-126 targets and the function they serve in carcinogenesis.…”
Section: Discussionsupporting
confidence: 52%
“…miR-126 is downregulated and acts as a tumor suppressor in stomach cancer (27). A previous study by our group also found that miR-126 acted as a tumor suppressor in gastric carcinoma, and PLK2 was a target gene of miR-126 (28). This therefore indicated that the upregulation of PLK2 in gastric cancer may be associated with the downregulation of miR-126; thus, miR-126 may also have a dominant role in gastric cancer.…”
Section: Discussionmentioning
confidence: 52%